2019
DOI: 10.31299/hrri.54.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies in students with physical disabilities – predictive role of self-esteem, general self-efficacy and basic hope

Abstract: Uzimajući u obzir osobne i okolinske prepreke, osobe sa stečenim fizičkim teškoćama prolaze kroz mnoge stresne situacije. U radu se ispituju strategije suočavanja koje rabe studenti s tjelesnim teškoćama. Cilj je ispitati korelaciju između uvjerenja o sebi i svijetu (samopoštovanje, samopouzdanje i nadanje) i strategija suočavanja kod studenata s fizičkim teškoćama. U istraživanju je sudjelovalo 111 studenata sa stečenim fizičkim teškoćama uključujući ozljede kralježnične moždine i različite druge teškoće s kr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
1
5
0
2
Order By: Relevance
“…In this study, spiritual coping was the most frequently used coping style among study participants which was consistent with coping strategies among Poland students with physical disabilities revealing that beliefs about oneself, the world, and basic hope to contribute to explaining variations in the nature and strength of persons coping strategies [48]. In the present study, spirituality is the most frequently used coping strategy among the participants from the emotional-focused subscale.…”
Section: Discussionsupporting
confidence: 82%
“…In this study, spiritual coping was the most frequently used coping style among study participants which was consistent with coping strategies among Poland students with physical disabilities revealing that beliefs about oneself, the world, and basic hope to contribute to explaining variations in the nature and strength of persons coping strategies [48]. In the present study, spirituality is the most frequently used coping strategy among the participants from the emotional-focused subscale.…”
Section: Discussionsupporting
confidence: 82%
“…Basic hope is a fundamental belief in two features of the world: its order and sense and general positivity toward humans (Trzebiński & Zięba, 2004). Basic hope positively correlates with disability acceptance, (Byra, 2014) posttraumatic growth, (Byra, 2018a), problem-solving coping (Byra, 2016), self-efficacy, and negatively with avoidance and emotion-focused coping in people with SCI (Byra & Ćwirynkało, 2018). Previous studies have shown a significant correlation between basic hope and coping strategies in people with long-term SCI (Byra, 2016).…”
Section: Hope As a Predictormentioning
confidence: 99%
“…In addition, low levels of self-efficacy can be a primary risk factor for maladaptive adjustment in people with SCI (Craig et al, 2013). General self-efficacy is also an important determinant of coping with the encountered challenges (Bhattarai et al, 2018; Byra & Ćwirynkało, 2018; Umucu et al, 2016). Women with SCI have been found to have lower general self-efficacy than men (Byra, 2011).…”
Section: Self-efficacy As a Moderatormentioning
confidence: 99%
“…Svojom isprepletenošću mogu imati snažan učinak na emocionalno blagostanje osobe djelujući time i na ostale dimenzije kvalitete života poput fizičkog i mentalnog zdravlja, obiteljskog i radnog okruženja te socijalnih interakcija [5,8]. Pritom pozitivno promišljanje, nadanje, samopoštovanje, samoefikasnost, otpornost na stresne podražaje, socijalna osjetljivost i podrška mogu imati dodatne učinke [11,12].…”
Section: Aspects Of Physical Disabilityunclassified
“…With their intertwining, they strongly affect a person's emotional well-being, thereby affecting other dimensions of quality of life, such as physical and mental health, family and work environment, and social interactions [5,8]. At the same time, positive reflection, hope, self-esteem, self-efficacy, resistance to stressful stimuli, social sensitivity, and support can have additional effects [11,12]a scale to measure the coping strategies used by people with disabilities to face the disability-related difficulties (caused by both disability itself and by stigma.…”
Section: Aspects Of Physical Disabilitymentioning
confidence: 99%